Sustainability indicators proposal for vine production in Mendoza, Argentina - Abraham, Laura; Alturria, Laura; Fonzar, Alfredo; Ceresa, Alejandro; Arnés, Esperanza (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The concept of sustainability implies a long-term relationship between human been and nature. Sustainable production systems are those systems capable of remaining in the time since they promote the conservation of natural resources, social capital and generate enough economic rents to support themselves. Growing vine and wine activities in Mendoza (Argentina) provide numerous benefits to the agricultural sector which is responsible for the use and pollution of natural resources. There are several indicators that show information of the viticulture sector, but most of them focus on physical and economic aspects. This work consists in the selection of indicators based on the theoretical concept of sustainability that request to integrate the three system’s dimensions: economic, social and environmental. This was applied to the viticulture sector in Mendoza, therefore indicators were designed which are able to characterize it following the concept of sustainability. The selected indicators resulted appropriate to describe the grade of sustainability in every dimension (social, economic and environmental) aspects and were easy to obtain and to understand.